Soil test crop response nutrient prescription equations for improving soil health and yield sustainability—a long-term study under Alfisols of southern India - Murthy, R. Krishna; Nagaraju, Bhavya; Govinda, K.; Uday Kumar, S. N.; Basavaraja, P. K.; Saqeebulla, H. M.; Gangamrutha, G. V.; Srivastava, Sanjay; Dey, Pradip (Frontiers in Plant Science, 2024)
Introduction: Enhancing soil health and nutrient levels through fertilizers boosts agricultural productivity and global food security. However, careful fertilizer use is essential to prevent environmental damage and improve crop yields. The Soil Test Crop Response (STCR) is a scientific approach to fertilizer recommendation which ensures efficient use, supporting higher crop production while protecting the environment and preserving resources. Methodology: A long-term field experiment on soil test crop responseSTCR-based fertilizer recommendationapproach was initiated in 2017 at the Zonal Agriculture Research Station,